In memory of Augusto Vigna Taglianti (1943-2019) - Carpaneto, Giuseppe Maria; Bologna, Marco Alberto; Audisio, Paolo; Biondi, Maurizio; Zapparoli, Marzio (Fragmenta entomologica, 2019)
On the evening of June 7th, 2019, Augusto Vigna Taglianti died in Rome at the age of almost 76 years, after a long illness, tenderly assisted by his wife Giuliana. Formerly a Professor of Entomology at the Sapienza University of Rome, he was a Full Member of the Italian National Academy of Entomology and of the National Academy of Sciences (the “Accademia dei XL”) [...]